Prospek Budidaya Maggot (Larva Black Soldier Fly) untuk Membangun Ekonomi Desa dan Mengurangi Sampah Rumah Tangga - Hakim, Mukti; Balatif, Fuad; Siregar, Ira Pratiwii (UNIVERSITAS LABUHANBATU, 2023)
Indonesia has quite serious environmental problems, one of which is the waste problem, waste production in Indonesia is always increasing every day, both organic and inorganic waste. One of the organic waste recycling techniques is the bioconversion method. Organisms that play a role in the bioconversion process can be fungi or insect larvae. These BSF larvae are known as maggots or